Pengaruh Model Pembelajaran Berbasis Proyek (Project Based Learning) Terhadap Kreativitas Siswa Pada Materi Sistem Reproduksi Manusia Kelas XI SMA/MA - Febby Erna Sari Lubis; Indayana Febriani Tanjung; Lailatun Nur Kamalia Siregar (LPPM Politeknik Pratama, 2023)
The project learning model involves students to collaborate, solve problems by stimulating their imagination and creativity to complete a project. This study aims to determine the effect of the project-based learning model on student creativity in the human reproductive system material for class XI SMA/MA. The research method used in this study uses a quasi-experimental or quasi-experimental. The data analysis used is data prerequisite test and hypothesis testing which includes independent sample t test. The research population was all students of class XI MIA at MAS PAB 1 Sampali. The sampling technique uses total sampling. The results of the study with the independent sample t test showed that tcount was worth 4,459 and ttable 1,66 so that it showed tcount > tttable where Ha was accepted which concluded that there was an influence of Project Based Learning Models on Student Creativity in Reproductive System Material Human Class XI SMA / MA.